Microscale Laser Surgery Demonstrates the Grasping Function of the Male Sex Combs in Drosophila melanogaster and Drosophila bipectinata. (22nd September 2014) - Hurtado‐Gonzales, Jorge L.; Gallaher, Wesley; Warner, Alexandra; Polak, Michal; Zeh, D.
Abstract Male secondary sexual traits of animals are richly diversified in form and complexity, yet there are many species in which their precise function remains unknown. Within the genus Drosophila, species belonging to the melanogaster and obscura species groups have evolved a remarkable variety of sex combs, male‐limited secondary sexual traits located on the tarsi of both front legs. Information concerning sex comb function is minimal or absent, except for D. melanogaster, where previous studies indicate that the sex combs are used for grasping the female prior to copulation. These studies, however, do not unambiguously demonstrate comb function, because it has not been possible to ascribe observed behavioral outcomes of the various comb manipulations to changes in the combs per se. We used microscale laser surgery to manipulate comb size in D. melanogaster and D. bipectinata, and tested the hypothesis that the sex combs function as grasping devices in courtship, making them essential for copulation to ensue. Results of high‐resolution behavioral analysis in small observation arenas demonstrated that in both species in which sex combs were surgically eliminated, males were unable to grasp, mount or copulate. The combless foretarsi of these altered males slipped off the end (D. melanogaster) and sides (D. bipectinata) of the female abdomen when courting males attempted to grasp. In most cases, males whose sex combs were reduced but not completely removed exhibited similar copulation probabilities as surgical control males, a result we demonstrated in observation chambers as well as under more ecologically realistic conditions inside population cages where males and females interacted on the surface of fruit substrates. Thus, the sex combs in D. melanogaster and D. bipectinata are grasping devices, essential for mounting and copulation.